2007
DOI: 10.1016/j.freeradbiomed.2007.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species and cellular oxygen sensing

Abstract: Many organisms activate adaptive transcriptional programs to help them cope with decreased oxygen levels, or hypoxia, in their environment. These responses are triggered by various oxygen sensing systems in bacteria, yeast and metazoans. In metazoans, the hypoxia inducible factors (HIFs) mediate the adaptive transcriptional response to hypoxia by upregulating genes involved in maintaining bioenergetic homeostasis. The HIFs in turn are regulated by HIF-specific prolyl hydroxlase activity, which is sensitive to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(111 citation statements)
references
References 84 publications
(99 reference statements)
6
102
0
3
Order By: Relevance
“…Reactive oxygen species (ROS) is another factor implicated in HIF1A accumulation. Evidence suggests that ROS increases HIF1A by directly inhibiting PHD catalytic activity (Cash et al 2007, Kaelin & Ratcliffe 2008. Finally, reports have also suggested that hypoxia can act independently of the HIF1A transcription factor (Bindra et al 2005, Arany et al 2008, Fujisaka et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) is another factor implicated in HIF1A accumulation. Evidence suggests that ROS increases HIF1A by directly inhibiting PHD catalytic activity (Cash et al 2007, Kaelin & Ratcliffe 2008. Finally, reports have also suggested that hypoxia can act independently of the HIF1A transcription factor (Bindra et al 2005, Arany et al 2008, Fujisaka et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Salnikow, et al (Salnikow et al, 2005) have proposed that divalent cations such as cobalt and nickel increase HIF-1α protein by oxidizing and thus depleting cellular ascorbate. Ascorbate is the preferred electron donor to the prolyl-4-hydoxylase (EC 1.14.11.2) that is responsible for hydroxylating HIF-1α, which then targets it for destruction in the ubiquitin-proteosome system (Cash et al, 2007). Without ascorbate, this hydroxylation would not occur and HIF-1α would accumulate.…”
mentioning
confidence: 99%
“…However, the importance of ROS either as therapeutic, cytotoxic molecule or as signaling molecule under the different oxygen conditions in a tumor and its specific relevance for the outcome to therapy are not clear. In fact, it has been convincingly demonstrated that ROS levels either increase or decrease under hypoxic conditions 364,365,[371][372][373] . These contradictory effects have been associated with differences in the methodological approaches, in the cell types investigated, in the metabolic state of the cells, in the disease context, and so on.…”
Section: Ros and Redox Measurements And Research Potential In Oncologymentioning
confidence: 99%
“…However, none of these latter methods is specific for a certain type of ROS. In addition, ROS can also be determined in frozen tissues by staining with the fluorescent dyes such as DCF or DHE 364,372,373 . However, to date, the most specific approach to detect superoxide anion radicals and other free radicals intra-or extracellularly is based on electron spin resonance (ESR).…”
Section: Ros and Redox Measurements And Research Potential In Oncologymentioning
confidence: 99%